PENGARUH KEPEMILIKAN INSTITUSIONAL, INTENSITAS MODAL DAN UKURAN PERUSAHAAN TERHADAP AGRESIVITAS PAJAK(EMITEN SEKTOR BASIC MATERIALS BURSA EFEK INDONESIA PERIODE 2019-2023) - Ananta, Engela; Marundha, Amor; Maidani, Maidani (SINERGI : Jurnal Riset Ilmiah, 2025)
This study aims to examine and analyze the effect of institutional ownership, capital intensity and firm size on tax aggressiveness. The research method used is quantitative. The types and sources of data in this study are secondary data in the form of financial statements of companies listed on the Indonesia Stock Exchange (BEI) during the period 2019-2023. The sampling technique used is purposive sampling, with a total of 150 observation data samples. The data analysis in this study was conducted using Eviews 13. The results of this study explain that institutional ownership has a positive and significant effect on tax aggressiveness, capital intensity has a positive and significant effect on tax aggressiveness and firm size has a negative and significant effect on tax aggressiveness.